1992
DOI: 10.1007/bf00000875
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mechanisms of stone alteration carried out by filamentous fungi living in monuments

Abstract: Biochemical weathering mechanisms carried out by Penicillium frequentans and Cladosporium cladosporoides on unaltered sandstone, granite and limestone were studied using FTIR, X-ray diffraction, atomic absorption and flame photometry. Strains belonging to both fungal species, isolated from the facades of two Spanish Cathedrals, were used.Large amounts of oxalic, citric and gluconic acids were produced by P. frequentans in broth cultures. These metabolites caused extensive deterioration of clay silicates, micas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…quartz sand, crystalline quartz and commercial glass (Brehm et al, 2005). Microbial action is mainly indirect, through either the production of chelates or the production of acids (mineral or organic) or other metabolites, together with biomechanical effects (Cromack et al, 1979;De La Torre et al, 1992;Mandal et al, 2002). In bioweathering of rock silicates and aluminosilicates, cleavage of Si-O-Si (siloxane) or Al-O bonds or removal of cations from the silicate crystal lattice may cause collapse of the silicate lattice structure.…”
Section: Silicatesmentioning
confidence: 99%
“…quartz sand, crystalline quartz and commercial glass (Brehm et al, 2005). Microbial action is mainly indirect, through either the production of chelates or the production of acids (mineral or organic) or other metabolites, together with biomechanical effects (Cromack et al, 1979;De La Torre et al, 1992;Mandal et al, 2002). In bioweathering of rock silicates and aluminosilicates, cleavage of Si-O-Si (siloxane) or Al-O bonds or removal of cations from the silicate crystal lattice may cause collapse of the silicate lattice structure.…”
Section: Silicatesmentioning
confidence: 99%
“…As no direct physical attacks by fungal hyphae or cyanobacterial filaments were observable via microscopical methods (SEM, TEM, light microscopy) within mineral samples, an indirect process resulting from microbial metabolism is suggested. For example, production of organic acids or respiration-derived CO 2 would lower the pH, which is a possible factor in biodeterioration of minerals (Delatorre et al, 1993;Gómez-Alarcón et al, 1994;Machill et al, 1997;Weber et al, 2011). The fact that pH decreased only slightly and in the same way in all experiments despite varying extent of dissolution (Figure 3) is not contradictory with this explanation as pH values in the direct micro-environment of cells between a biofilm and its substrate can differ significantly from those in the macro-environment (Bonneville et al, 2011).…”
Section: Discussionmentioning
confidence: 76%
“…Excreted organic acids and respiration-derived CO 2 are often active in these processes (Silverman and Munoz, 1970;Delatorre et al, 1993;Gómez-Alarcón et al, 1994;Machill et al, 1997;Landeweert et al, 2001;Abdulla, 2009;Weber et al, 2011), although fungal hyphae can directly penetrate and widen fissures in rocks (Sterflinger, 2000;Gorbushina et al, 2003;Chertov et al, 2004). The extreme microbial diversity of soil organisms (Jongmans et al, 1997;Landeweert et al, 2001;Schöll et al, 2008;Abdulla, 2009;Bonneville et al, 2009;Rosling et al, 2009;Taylor et al, 2009) and accompanying macroscopic vegetation results in high rates of weathering.…”
Section: Introductionmentioning
confidence: 99%
“…In the natural conditions, it is difficult to recognize the discoloration problems conferred to fungi and the same ones conferred to autotrophs because these organisms grow in the same places. Chemical deterioration induced by fungi is due to the production of a wide range of acids such as acetic, oxalic, glucuronic, fumaric and citric acid [5,67,[75][76][77], involved in the demineralization of various substrates. It was observed that fungi are infrequent biomass on stone and prefer painted surfaces [5,64].…”
Section: Biodeterioration Mechanism By Fungimentioning
confidence: 99%